A mini-review on ancient mathematics’ modern applications with an emphasis on the old Babylonian mathematics for MEMS systems - Niu, Jing-Yan; Feng, Guang-Qing (Frontiers in Physics, 2024)
This paper offers a concise overview regarding ancient Chinese mathematics, centering on the Ying Buzu Shu, He Chengtian inequality, and the frequency formulation stemming from them. Moreover, it delves into the Max-min approach and Chunhui He’s iterative algorithm. What’s more, the spotlight is cast on ancient Chinese mathematics, which bears certain similarities to the ancient Babylonian mathematical tradition. Subsequently, the old Babylonian algorithm for computing square roots is adapted to tackle the hurdle of nonlinear differential equations. To showcase the potential of this approach, a set of Micro-Electro-Mechanical systems (MEMS) problems are utilized to exemplify the effectiveness of the modified old Babylonian algorithm in attaining high-precision analytical solutions, accompanied by an exploration of its prospective applications.